Progression patterns and risk factors of axial elongation in young adults with nonpathologic high myopia: three-year large longitudinal cohort follow-up - Kong, Kangjie; Jiang, Jingwen; Wang, Peiyuan; Song, Yunhe; Lin, Fengbin; Li, Fei; Gao, Xinbo; Liu, Xiaoyi; Jin, Ling; Wang, Zhenyu; Liu, Yuhong; Chen, Meiling; et al. (American journal of ophthalmology, 2024)
Purpose - To investigate the progression patterns and risk factors of axial elongation in young adults with nonpathologic high myopia. - Design - Prospective, clinical observational cohort study with 2- to 4-year follow-up. - Methods - A total of 1043 eyes of 563 participants (3515 medical records) aged 18 to 50 years with nonpathologic high myopia (axial length [AL] ≥ 26 mm; myopic maculopathy < diffuse chorioretinal atrophy; without posterior staphyloma) were included from 1546 participants (6318 medical records). Annual axial elongation was calculated via linear mixed-effect models. The associated risk factors of axial elongation were determined by ordinal logistic regression analysis, with generalized estimate equations for eliminating an interocular correlation bias. - Results - Based on 5359 times of AL measurements, the annual axial elongation of participants (mean [SD] age 31.39 [9.22] years) was 0.03 mm/year (95% confidence interval [CI], 0.03-0.04; P < .001) during a 30.23 (6.06) months’ follow-up. Severe (>0.1 mm/year), moderate (0.05-0.09 mm/year), mild (0-0.049 mm/year), and nil (≤0 mm/year) elongation was observed in 122 (11.7%), 211 (20.2%), 417 (40.0%), and 293 (28.1%) eyes. The following risk factors were significantly associated with axial elongation: baseline AL ≥ 28 mm (odds ratio [OR], 4.23; 95% CI, 2.95-6.06; P < .001); age < 40 years (OR, 1.64; 95% CI, 1.18-2.28; P = .003); axial asymmetry (OR, 2.04; 95% CI, 1.26-3.29; P = .003), and women (OR, 1.52; 95% CI, 1.13-2.2.05; P = .006). Using antiglaucoma medications was a protective factor (OR, 0.46; 95% CI, 0.27-0.79; P = .005), which slowed 75% of axial elongation from 0.04 (0.06) to 0.01 (0.06) mm/y (P < .001). - Conclusions - Axial elongation continued in young adults with nonpathologic myopia. Risk factors included longer baseline AL and axial asymmetry, younger age, and woman. Topical use of antiglaucoma medications may be useful to reduce ongoing axial elongation.
Online verfügbar: 14. August 2024, Artikelversion: 9. September 2024
Gesehen am 26.11.2024